2020
DOI: 10.12890/2020_001764
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic Acute Cholecystitis

Abstract: The authors present the case of a 51-year-old woman with no history of surgical or traumatic injury or accident, who presented with right hypochondrium and epigastric discomfort, malaise, nausea, loss of appetite and episodes of dark urine and greenish stools. Initial laboratory work-up revealed elevated inflammatory markers including leucocytosis with left shift and C-reactive protein, and a slight elevation of gamma-glutamyltransferase and alkaline phosphatase, with no other significant alterations. Computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In type 4, poor gallbladder mesenteric attachment may occur, as in cases of liver atrophy or cirrhosis, peritoneal fat loss secondary to aging, and weight loss [7,13,20,21]. These abnormal attachments predispose the gallbladder to torsion, herniation, strangulation, and increased stone formation [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Floating Gallbladdermentioning
confidence: 99%
See 3 more Smart Citations
“…In type 4, poor gallbladder mesenteric attachment may occur, as in cases of liver atrophy or cirrhosis, peritoneal fat loss secondary to aging, and weight loss [7,13,20,21]. These abnormal attachments predispose the gallbladder to torsion, herniation, strangulation, and increased stone formation [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Floating Gallbladdermentioning
confidence: 99%
“…Kim et al [5] reviewed fourteen cases and reported only four cases of gallbladder herniation with GBV; the remaining ten cases had gallbladder herniation with acute cholecystitis. Floating gallbladder may herniate into anterior abdominal wall defects [25,[27][28][29][30][31][32], most commonly parastomal gallbladder herniation [29]. Unusual gallbladder herniations are also reported in the literature.…”
Section: Gallbladder Herniationmentioning
confidence: 99%
See 2 more Smart Citations